Schizandrin C regulates lipid metabolism and inflammation in liver fibrosis by NF-κB and p38/ERK MAPK signaling pathways - Chen, Panpan; Wang, Rong; Liu, Fangbin; Li, Shengnan; Gu, Yanqiu; Wang, Lei; Yuan, Yongfang (Frontiers in Pharmacology, 2023)
Liver fibrosis is considered a sustained wound healing response and metabolic syndrome, and its therapy is of great significance for chronic liver disease. Schizandrin C, as one lignan from hepatic protectant Schisandra chinensis, can depress the oxidative effect and lipid peroxidation, and protect against liver injury. In this study, C57BL/6J mice were used to estimate a liver fibrosis model by CCl4, and Schizandrin C exerted an anti-hepatic fibrosis effect, as evidenced by decreased alanine aminotransferase, aspartate aminotransferase and total bilirubin activities in serum, lower hydroxyproline content, recuperative structure and less collagen accumulation in the liver. In addition, Schizandrin C reduced the expressions of alpha-smooth muscle actin and type Ι collagen in the liver. In vitro experiments also revealed that Schizandrin C attenuated hepatic stellate cell activation in both LX-2 and HSC-T6 cells. Furthermore, lipidomics and quantitative real-time PCR analysis revealed that Schizandrin C regulated the lipid profile and related metabolic enzymes in the liver. In addition, the mRNA levels of inflammation factors were downregulated by Schizandrin C treatment, accompanied by lower protein levels of IκB-Kinase-β, nuclear factor kappa-B p65, and phospho-nuclear factor kappa-B p65. Finally, Schizandrin C inhibited the phosphorylation of p38 MAP kinase and extracellular signal-regulated protein kinase, which were activated in the CCl4 fibrotic liver. Taken together, Schizandrin C can regulate lipid metabolism and inflammation to ameliorate liver fibrosis by nuclear factor kappa-B and p38/ERK MAPK signaling pathways. These findings supported Schizandrin C as a potential drug for liver fibrosis.